The Irish in England - Neil Cummins; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2022)
The successful assimilation of ethnic minorities into Western economies is one of the biggest challenges facing the Modern World. The substantial flows of Irish, to England, provide an historical example of this process. However, this has received surprisingly little scholarly attention. We use the universe of probate and vital registers of births, marriages and deaths, from England, 1838 to 2018, to document the status of the Irish in England. We identify the 'Irish' in the records as those individuals with distinctively Irish surnames. From at least the mid 19th century to 2018, the Irish in England have persisted as an underclass, 30-50% poorer than the English. Infant mortality is about 25% higher for the Irish 1838- 1950 but has subsequently equalized. We discuss the potential roles of selective migration, social mobility, discrimination, and the role of the marriage market in this, and signpost directions for future research.
Keywords: N00; N33; N34; 330; inequality; economic history; big data